Scientific Reasoning Skill and Multiple Representations in Education Research During Last Ten Years: A Review Bibliometric Study (2013-2022) and the Contribution of Indonesia - Wicaksono, Iwan; Ma'rof, Aini Marina; Mahardika, I Ketut; Rosida, Rina Fatiya; Erlina, Nia (Indonesia Approach Education, 2024)
The development of scientific literacy in education relies heavily on two fundamental capabilities: scientific reasoning, which enables systematic analysis and evidence-based conclusions, and multiple representations, which facilitate understanding through diverse forms of concept presentation. Despite their importance, no comprehensive analysis has mapped the research landscape connecting these crucial educational components. This study conducted a bibliometric analysis of research trends in scientific reasoning and multiple representations published between 2013-2022. A systematic search using Google Scholar yielded 392 relevant articles (234 focusing on scientific reasoning, 158 on multiple representations), which were analyzed using VOSviewer visualization software. The analysis revealed five distinct research clusters: (1) scientific reasoning and knowledge development, emphasizing theoretical foundations; (2) multiple representations in education, focusing on pedagogical applications; (3) student learning in physics, highlighting discipline-specific implementations; (4) scientific reasoning skills analysis, examining assessment methods; and (5) chemistry and inductive reasoning, exploring subject-specific reasoning patterns. Indonesian researchers made significant contributions to the field, particularly in developing innovative approaches to scientific reasoning skills and multiple representation strategies in science education. This analysis not only maps the current research landscape but also identifies promising directions for future studies, especially in developing integrated approaches that combine scientific reasoning development with multiple representation techniques in science education.